The Role of Legislative Science in the Formation of Fair and Effective Laws in Indonesia - Nadapdap, Binton Jhonson (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Legislation science plays a crucial role in forming fair and effective laws in Indonesia. The law-making process that is transparent and involves public participation will result in legal outcomes that are acceptable to all levels of society. This paper aims to explore how legislation science ensures that laws are aligned with the principles of justice, legal certainty, and effectiveness. The creation of fair laws requires the legislative process to consider not only formal legal aspects but also the existing social context. This research adopts a descriptive- analytical approach to explain the role and challenges of implementing legislation science in Indonesia.